Role of Protein Misfolding and Proteostasis Deficiency in Protein Misfolding Diseases and Aging - Karina Cuanalo-Contreras; Abhisek Mukherjee; Claudio Soto (International Journal of Cell Biology)
The misfolding, aggregation, and tissue accumulation of proteins are common events in diverse chronic diseases, known as protein misfolding disorders. Many of these diseases are associated with aging, but the mechanism for this connection is unknown. Recent evidence has shown that the formation and accumulation of protein aggregates may be a process frequently occurring during normal aging, but it is unknown whether protein misfolding is a cause or a consequence of aging. To combat the formation of these misfolded aggregates cells have developed complex and complementary pathways aiming to maintain protein homeostasis. These protective pathways include the unfolded protein response, the ubiquitin proteasome system, autophagy, and the encapsulation of damaged proteins in aggresomes. In this paper we review the current knowledge on the role of protein misfolding in disease and aging as well as the implication of deficiencies in the proteostasis cellular pathways in these processes. It is likely that further understanding of the mechanisms involved in protein misfolding and the natural defense pathways may lead to novel strategies for treatment of age-dependent protein misfolding disorders and perhaps aging itself.